Reflection of random Creation in institution of university education in the stagflation implications - ابراهيم, خليل اسماعيل (Journal of Economics and Administrative Sciences, 2016)
AbstractSince period the developing economies  including, Iraq economy faced undesirable double economic which is spread unemployment beside continual rising  in price levels this phenomenon called stagflation , there is researches  deal with this phenomenon and the elements participate in it, but it seems to the researcher there is important element from These elements which did not give sufficient concern and this lead to unhealthy situation  which can be represent to the rush creating establishments to University education in Iraq during period ( 2004- 2014) with excessive the3 truly need of the outputs which the Iraq market need which result increase the numbers unemployed on one hand and the growing expenses for the possibility of providing academic seats in private colleges , on the other hand. The research reaching to number of result , the most important was, • The education field became material target more than science. • The frightful quantity of universities and colleges regard as important element in Deeping the stagflation phenomenon.